2016
DOI: 10.1186/s13071-016-1810-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-kβ factor Rel2 during Plasmodium falciparum and bacterial infection in Anopheles dirus

Abstract: BackgroundAnopheles mosquitoes transmit malaria which is one of the world’s most threatening diseases. Anopheles dirus (sensu stricto) is among the main vectors of malaria in South East Asia. The mosquito innate immune response is the first line of defence against malaria parasites during its development. The immune deficiency (IMD) pathway, a conserved immune signaling pathway, influences anti-Plasmodium falciparum activity in Anopheles gambiae, An. stephensi and An. albimanus. The aim of the study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…Moreover, two downstream molecules – LRP1 and BINT2 – are transmembrane proteins that in mammals and insects have overlapping functions in phagocytosis and adhesion (Mantuano, Jo, Gonias, & Campana, 2010; Moita, Vriend, Mahairaki, Louis, & Kafatos, 2006; Rabiej et al, 2016), and therefore, likely facilitate the adhesion of hemocytes to the heart. In this study, we also confirmed the positive role that REL2 plays in pathogen killing (Dekmak, Yang, Zu Dohna, Buchon, & Osta, 2021; Dong et al, 2011; Dong, Simões, & Dimopoulos, 2020; Frolet et al, 2006; Kambris et al, 2010; Khan, Liew, Leong, & Lau, 2016; Meister et al, 2009; Meister et al, 2005; Mitri et al, 2009; Schnitger, Kafatos, & Osta, 2007). When we systemically knocked down the expression of rel2 , bacteria proliferated uncontrollably during the later stages of infection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, two downstream molecules – LRP1 and BINT2 – are transmembrane proteins that in mammals and insects have overlapping functions in phagocytosis and adhesion (Mantuano, Jo, Gonias, & Campana, 2010; Moita, Vriend, Mahairaki, Louis, & Kafatos, 2006; Rabiej et al, 2016), and therefore, likely facilitate the adhesion of hemocytes to the heart. In this study, we also confirmed the positive role that REL2 plays in pathogen killing (Dekmak, Yang, Zu Dohna, Buchon, & Osta, 2021; Dong et al, 2011; Dong, Simões, & Dimopoulos, 2020; Frolet et al, 2006; Kambris et al, 2010; Khan, Liew, Leong, & Lau, 2016; Meister et al, 2009; Meister et al, 2005; Mitri et al, 2009; Schnitger, Kafatos, & Osta, 2007). When we systemically knocked down the expression of rel2 , bacteria proliferated uncontrollably during the later stages of infection.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, two downstream molecules -the low-densitylipoprotein-receptor-related protein LRP1 and the beta integrin BINT2 -are transmembrane proteins that in mammals and insects have overlapping functions in phagocytosis and adhesion (69)(70)(71), and therefore, likely facilitate the adhesion of hemocytes to the heart. In this study, we also confirmed the positive role that REL2 plays in pathogen killing (29,44,68,(72)(73)(74)(75)(76)(77)(78). When we systemically knocked down the expression of rel2, bacteria proliferated uncontrollably during the later stages of infection.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, two downstream molecules-the low-density-lipoproteinreceptor-related protein LRP1 and the beta integrin BINT2are transmembrane proteins that in mammals and insects have overlapping functions in phagocytosis and adhesion [69][70][71], and therefore, likely facilitate the adhesion of haemocytes to the heart. In this study, we also confirmed the positive role that REL2 plays in pathogen killing [29,44,68,[72][73][74][75][76][77][78]. When we systemically knocked down the expression of rel2, bacteria proliferated uncontrollably during the later stages of infection.…”
Section: Discussionsupporting
confidence: 79%
“…gambiae genome encodes two isoforms of the Relish homolog (i.e., REL-2); the short isoform, REL-2S, is involved in the response against Gram-negative bacteria, while the long isoform, REL-2F, against Gram-positives (Meister et al, 2005). It has been demonstrated that in Anopheles dirus REL-2F is involved in protection against both Gram-positive (with Lys-type peptidoglycan) and Gram-negative bacteria (with DAP-type peptidoglycan) (Khan et al, 2016). Relish, in turn, induces the expression of antimicrobial peptides (AMPs).…”
Section: Humoral Immune Responses Mediated By the Gut And Interactions With The Associated Microbiotamentioning
confidence: 99%